Respuesta :
1. To solve this problem, you need to remember that an exponential function has the following form:
f(x)=a^x
"a" is the base and "x" is the exponent.
2. It is important to know that the logarithmic functions and the exponential functions are inverse. Then, you have:
c=ln2
e^c=e^(ln2)
e^c=2
3. Therefore, the answer is:
e^c=2
f(x)=a^x
"a" is the base and "x" is the exponent.
2. It is important to know that the logarithmic functions and the exponential functions are inverse. Then, you have:
c=ln2
e^c=e^(ln2)
e^c=2
3. Therefore, the answer is:
e^c=2